Nascimento na sociedade Bororo : saberes e fazeres no tecer do corpo da mulher - Medeiros, Renata Marien Knupp (2015)
It´s been noticed, in recent years, a greater influx of indigenous pregnant women to give birth in urban centers. However, it is observed that, in the mainstream logic of procedures of the hospital system, based on the biomedical model, the care provided during labor and birth contrasts with the traditional indigenous practices and how the bodies are perceived in their different cultures. Currently living in Mato Grosso (MT) there are about 42.525 indigenous individuals belonging to 43 different people. Among them, the Bororo sum up to 2.348 individuals and have their territories located in five different cities. This study aimed to understand the traditional education processes that is perceived by Bororos with regards with body when experiencing conception, pregnancy, childbirth and postpartum. This is a qualitative, exploratory-descriptive, which is part of research on Social Movements, Politics and Popular Education of the Graduation Program in Education UFMT. To collect data, we used the methodological elements of ethnography as observation, field work reports and the ethnographic interviews. The subject was the Bororo population of the village of Córrego grande (Great stream), located in Santo Antonio do Leverger-MT. Based on contacts made in this space, there was an indication of women who experienced pregnancy and childbirth, as well as male and female elderly who educate and care for these women. By analyzing the material collected, the data were organized into two main categories. The first refers to the traditional education processes, which regards the Bororo body before, during and after pregnancy, and the second deals with biomedical practices introduced after the institutionalization of the Bororo birthprocess. The results indicate that the Bororo body education process is continuous and takes place in the village collective, being transmitted through oral, corporeality and observation and it is facilitated by the intergenerational relationship. During the pregnancy and infant period, the Bororo education dedicated to build healthy bodies, which is related to the teaching of moral and ethical values, and by making the practice of guards and a set of prescriptions and prohibitions which, if not met, could affect the health of parents and child, and impact the development of the person. After contact with the official medical model, the Bororo population began to access both traditional knowledge as biomedical knowledge with regard to the design, pregnancy, childbirth and postpartum. However, the growing process of medicalization has generated misunderstandings, especially the contradictions between hospital care provided and the expectations of this society. The fact that some traditional practices are no longer currently held in place to the other, typical of the biomedical model, leads to the perception among the Bororo, that the body of today is not what it used to. Thus, this research aims to bring contributions so that we can question the hegemonic practice of current birth care model as well as provide support for critical reflection of the importance and necessity of the establishment of intercultural dialogue in indigenous health care, especially the one aimed to pregnancy and childbirth.